2023
DOI: 10.1186/s12888-023-04698-9
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between components of hypoglycemia worries and avoiding hypoglycemia behavior in type 2 diabetes mellitus with hypoglycemia: a network analysis

Abstract: Background The fear of hypoglycemia in type 2 diabetes mellitus (T2DM) patients with hypoglycemia has seriously affected their quality of life. They are always afraid of hypoglycemia and often take excessive action to avoid it. Yet, researchers have investigated the relationship between hypoglycemia worries and excessive avoiding hypoglycemia behavior using total scores on self-report measures. However, network analysis studies of hypoglycemia worries and excessive avoiding hypoglycemia behavio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
1
0
2
Order By: Relevance
“…These findings are supported by prior research (Brown et al, 2019;Gül et al, 2021;Menekli & Şentürk, 2022;Sheikhi et al, 2020;Wu et al, 2023). In the current study, the hypoglycaemic confidence levels of patients with diabetes were moderate, and the hypoglycaemic confidence levels of patients with fear of experiencing hypoglycaemia were lower.…”
Section: Theme 3: Managing Hypoglycaemiasupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are supported by prior research (Brown et al, 2019;Gül et al, 2021;Menekli & Şentürk, 2022;Sheikhi et al, 2020;Wu et al, 2023). In the current study, the hypoglycaemic confidence levels of patients with diabetes were moderate, and the hypoglycaemic confidence levels of patients with fear of experiencing hypoglycaemia were lower.…”
Section: Theme 3: Managing Hypoglycaemiasupporting
confidence: 90%
“…The physiological and psychological symptoms experienced by patients due to hypoglycaemia may have caused the disruption in their daily lives. In a prior study, it was found that patients experiencing hypoglycaemia experienced fear and anxiety, and as a result, they severely restricted their social lives in order to avoid this (Wu et al., 2023). Restrictions in daily and social life can impair a patient's ability to fulfil diabetes self‐care and therefore jeopardise their health (Martyn‐Nemeth et al., 2019; Przezak et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…23 Türkiye'de DM'si olan yaşlı hastaların uyku kalitesinin değerlendirildiği çalışmada, hastaların %58,6'sında kötü uyku kalitesi olduğu görülmüştür. 24 Daha uzun diyabet süresi, daha yüksek hipoglisemik olay insidansı ve diyabetik komplikasyonlar, kötü uyku kalitesi ile anlamlı şekilde ilişkili olduğunu belirlemişlerdir. 25 Yapılan çalışmalarda görüldüğü gibi DM'si olan bireylerde uyku kalitesini olumsuz yönde etkileyen birçok faktör olabilir.…”
Section: Bulgularunclassified
“…Diğer maddelerden daha çok "Uyku sırasında hipoglisemi konusunda endişeleniyorum" ifadesini ele almanın, hipoglisemiden aşırı kaçınma davranışını azaltmada daha etkili olabileceği belirtilmiştir. 24 Tip 2 DM'si olan bireylerde hipoglisemi korkusu ile uyku kalitesi arasındaki etkinin nedenlerinin incelenmesinin uyku kalitesinin geliştirilmesinde faydalı olabileceği düşünülmektedir.…”
Section: Bulgularunclassified